From Legal Compliance to Spiritual Authenticity: The Role of Halal Certification in Shaping Muslim Tourists’ Experiences - Mochamad Sumpena; Nurul Hikmah; Fina Annisa; Warsidi (Universitas Muhammadiyah Surakarta, 2026)
This study examines how halal regulations function as a moral and legal bridge between faith and consumer rights in religious tourism. Using a qualitative descriptive case study in Surabaya, Indonesia, this study explores how halal certification shapes Muslim tourists’ perceptions of trust, authenticity, and spiritual experience. Data were collected through in-depth interviews with eight key informants, including local and international Muslim tourists, business owners, hotel managers, and government officials, supported by document analysis of halal policies and certification frameworks. The findings indicate that halal regulations significantly strengthen tourists’ sense of spiritual security, ethical trust, and overall satisfaction. Halal certification is perceived not merely as legal compliance with Islamic principles, but also as a symbol of integrity, transparency, and respect for religious identity. Nevertheless, the study identifies key challenges, such as weak institutional coordination, limited halal literacy, and the risk of excessive commercialization of religious symbols. These issues highlight the importance of integrating legal, ethical, and spiritual dimensions within halal governance. The study concludes that sustainable halal tourism requires a careful balance between formal regulatory assurance and genuine spiritual authenticity. By integrating halal regulatory frameworks, perceived spiritual authenticity, and consumer trust, this study contributes to the halal tourism literature and offers strategic insights for policymakers and destination managers to strengthen institutional collaboration, enhance halal literacy, and promote ethical governance to support credible and sustainable halal tourism development.